Struktur dan Fungsi Pantun dalam Teks Pidato Pasambahan Acara Maminang Masyarakat Nagari Kapuh Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan - Kartika, Gisti; Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to describe the structure and function of pantun in the text of the pasambahan speech at the Maminang event of the Nagari Kapuh community, Koto XI Tarusan District, Pesisir Selatan Regency. The structure of pantun in this study consists of introduction, purpose or content, and closing. The function of pantun in this study consists of expressive function, directive function, and aesthetic function. This research is a literary research in the field of oral literature using descriptive method. The research informants amounted to three people who were the indigenous people of Nagari Kapuh. The research instrument is the researcher himself. There are three techniques used in data collection, namely field studies, interviews, and documentation. The data validation uses triangulation techniques. After all the data were collected, several stages were carried out, namely the transcription stage, transliteration, classification and analysis stage, and the reporting stage. The results of this study show that there are 5 couplets of pantun that belong to the introductory part, 11 couplets of pantun that belong to the part of conveying the purpose or content, 4 couplets of pantun that belong to the closing, 11 couplets of pantun that belong to the expressive function, 8 couplets of pantun that belong to the directive function, and 6 couplets of pantun that belong to the aesthetic function.